2011
DOI: 10.3389/fneur.2011.00064
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Embolization of Head and Neck Tumors

Abstract: Endovascular tumor embolization as adjunctive therapy for head and neck cancers is evolving and has become an important part of the tools available for their treatment. Careful study of tumor vascular anatomy and adhering to general principles of intra-arterial therapy can prove this approach to be effective and safe. Various embolic materials are available and can be suited for a given tumor and its vascular supply. This article aims to summarize current methods and agents used in endovascular head and neck t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 23 publications
0
59
0
1
Order By: Relevance
“…The first reported transcatheter embolization was performed in 1972 to stop bleeding from a duodenal hemorrhage using an autologous clot . Since then, development of embolic agents has advanced significantly and clinical applications have expanded to include, among others, the occlusion of arteriovenous malformations (AVMs), occlusion of arterial aneurysms, control of gastrointestinal bleeding, control of traumatic bleeding, treatment of postsurgical varicoceles, devascularization of head and neck tumors, and chemoembolization of solid organ tumors . The choice of embolic agent for a particular application is determined by the size of the vessel to be occluded, whether the occlusion is intended to be temporary or permanent, and the intended survival of the tissues supplied by the target vessel .…”
Section: Introductionmentioning
confidence: 99%
“…The first reported transcatheter embolization was performed in 1972 to stop bleeding from a duodenal hemorrhage using an autologous clot . Since then, development of embolic agents has advanced significantly and clinical applications have expanded to include, among others, the occlusion of arteriovenous malformations (AVMs), occlusion of arterial aneurysms, control of gastrointestinal bleeding, control of traumatic bleeding, treatment of postsurgical varicoceles, devascularization of head and neck tumors, and chemoembolization of solid organ tumors . The choice of embolic agent for a particular application is determined by the size of the vessel to be occluded, whether the occlusion is intended to be temporary or permanent, and the intended survival of the tissues supplied by the target vessel .…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative angiography is useful for surgical planning and embolisation to reduce blood loss during surgery. [15][16][17] Over the years, advancement in preoperative and operative techniques has resulted in fewer complications. 8 18 Radiotherapy-this is less invasive, associated with fewer complications, and highly effective for the control of symptoms and local disease.…”
Section: Discussionmentioning
confidence: 99%
“…This enhancement, in turn, may result in lower long-term recurrence risk. 27 Smaller tumors confined to the nasal cavity may be resected without embolization, especially if the internal maxillary artery can be addressed at the beginning of the resection. Larger tumors, particularly those with sphenoid or intracranial extension, benefit from embolization, though a small comparison study in the endoscopic era has not demonstrated an added benefit to embolization.…”
Section: Indications For Embolizationmentioning
confidence: 99%